MONITORING IN STATE AND NON-STATE PRESCHOOL EDUCATIONAL ORGANIZATIONS - Botirova Zukhrakhon Abdurakhimovna (Zeta Repository, 2023)
The article clarifies the content of the following concepts: "pedagogical monitoring"; "quality of preschool education"; the parameters, criteria and indicators of monitoring the quality of the organization of educational activities of a preschool educational institution are determined. Monitoring of the quality of the organization of educational activities of preschool educational institutions has been developed, which ensures the effective functioning and development of the system of preschool education.